Insight and capacity to consent to electroconvulsive therapy. (October 2019) - Scott, Russ; Prowacki, Steve
Objective: To critically examine a recent decision of the Victorian Supreme Court that found that the Mental Health Tribunal and the Victorian Civil and Administrative Tribunal erred in the application of the capacity test in the Mental Health Act 2014 (Vic) and that compulsory electroconvulsive therapy would infringe upon the human rights of two patients who had no insight into their chronic schizophrenia. Conclusions: After considering the concepts of insight and capacity to consent to treatment, the paper concludes that the decision in NJE and PBU v Mental Health Tribunal [2018] VSC 564 is problematic clinically.